Democratic Policing Manivestasi Independensi Polri dan Implementasi Perubahan Ligkungan Strategis di Era Demokrasi - Hutagalung, Reynold EP (Jurnal Keamanan Nasional, 2017)
Indonesia has decided to choose democracy as a road map to the people’s welfare as mandated by the constitution. Police who now live in the era of democracy, must secure the path of democracy in Indonesia. Implementation of the principles of democratic policing, is a necessity for the Police, for the sake of the functioning and the role of the Police as the Reformation wanted in 1998. One of the answers for democratic policing to achieve optimum results is to strengthen police and community partnerships.